GE_GERICHTE C/8968/2014 vom 14. Juni 2018 - GE Cour de justice (2018)
VENTE D'IMMEUBLE ; DÉFAUT DE LA CHOSE ; ACTION EN RÉDUCTION DU PRIX ; RESPONSABILITÉ CONTRACTUELLE | CO.97; CO.197; CO.205; CO.221; LEaux-GE.89